Integrating Islamic Values into Ecological Communication: A Perspective from the Bone Community - Rusnali, Andi Nur Aisyah; Syam, Syahrianti; Mandalia, Siska; A'la, Bassam Abul (Islamica: Jurnal Studi Keislaman, 2025)
This study analyzes the Mappano Bine tradition in Bone Regency as a communicative practice that integrates local wisdom, Islamic values, and ecological ethics. Drawing on a qualitative design with interviews, non-participant observation, and document analysis, the research examines how environmental communication is enacted through ritual performances, symbolic expressions, and collective practices. The findings indicate that Mappano Bine extends beyond agricultural celebration; it serves as a communicative act that weaves Islamic spirituality prayer, gratitude, and communal responsibility into indigenous ritual forms. These practices generate ecological consciousness and transmit environmental ethics across generations through oral narratives, ritual symbols, and communal participation. The study advances the field of environmental communication by framing Mappano Bine as a hybrid communicative model where religious and indigenous values converge to promote ecological harmony and cultural continuity. While challenges such as modernization and youth disengagement persist, the contribution lies in positioning ritual as an analytical lens for understanding the intersection of faith, culture, and ecological communication.